TRANSFORMATION OF THE IMAGE OF «TURGENEV’S GIRL» IN MODERN RUSSIAN PROSE. (International journal of artificial intelligence, 2026)
The goal of the article is to carry out an intertextual analysis of a number of modern prose texts and their fragments written in the end of XX and the beginning of the XXI centuries. Such an analysis allows to determine if the general understanding of the female image has changed in literature and to show the differences in description of a female character in the works of the writers of the end of XX and the beginning of the XXI centuries. V. Erofeev presents for the Russian reader a new kind of strong deep female image. His heroine bears the features of sacrifice and self-denial employed by the writers of the XIX century. L. Ulitskaya significantly changes Turgenev’s Asya; introducing into her story a secondary character with a similar name she adds to the image of the «Turgenev’s girl» a thirst for material prosperity and absolute spiritual rigidity. S. Streltsov explores the problems of becoming an ideal: he shows the possibility of any person, even orphans from America, to achieve a standard image praised by Turgenev. Post-modern writers V. Kuritsyn and E. Popov in their texts show skeptical attitudes towards Turgenev’s heroines, poke fun at them considering them completely obsolete and unnecessary here and now. A deep study of the classical literature and its remake make contemporary authors once again emphasize the «museum nature» of the classical literature and its isolation from the life of the XX–XXI centuries.